Should we have voluntary censorship code for Netflix? - Islam, Md. Zahidul (New Straits Times Press (M) Bhd., 2019)
NETFLIX allows customers to watch television shows, movies, documentaries on Internet-connected devices, such as tablets, computers, mobile phones and smart TVs.